Upaya Meningkatkan Hasil Belajar Siswa melalui Penggunaan Model Pembelajaran Discovery Learning pada Mata Pelajaran IPA SMP - Pratiwi, Heni Dwi; Putri, Rahmah Evita; Yenira, Fitria (TSAQOFAH, 2025)
This study is based on the low academic achievement of students in science subjects in Class IX at SMP Negeri 10 Padang, where learning outcomes have not met the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal). The purpose of this research is to improve student learning outcomes through the application of the Discovery Learning model. The study employed a Classroom Action Research (Penelitian Tindakan Kelas) method conducted in two cycles, involving 32 students from Class IX.1. Data were collected through multiple-choice written tests administered at the end of each cycle and analyzed by calculating the percentage of individual and class-wide mastery. The results showed an increase in the average student score from 63.6 with 43.75% mastery in the pre-cycle, to 73 with 65.6% mastery in the first cycle, and a significant improvement in the second cycle with an average score of 78.75 and 90.6% mastery. These findings demonstrate that the Discovery Learning model is effective in improving student learning outcomes. This model encourages students to actively discover concepts independently, leading to deeper understanding of the material and positively impacting academic performance. Therefore, Discovery Learning is a viable alternative instructional strategy for science education that emphasizes active engagement and conceptual understanding.